ETHERSTWEB – An Ethereum-Based Distributed Application for User Information Trustworthiness Verification - Koa, Chong-Gee; Heng, Swee-Huay; Chin, Ji-Jian (International Journal of Membrane Science and Technology, 2023)
Fake news and misinformation are prevalent on the Internet in this day and age. The popularity of social media such as Facebook, Instagram, TikTok has encouraged the people to share news or information over Internet without knowing whether it is a truth or fake information. The outbreak of COVID-19 affected the social activities of all levels of society as people were asked to stay at home to self-quarantine. It indirectly encourages the growth of the social activities online. Even though COVID- 19 is no longer a big threat to the world, people already used to rely on the Internet for the daily activities. Therefore, the trustworthy of the information on the Internet is getting crucial. ETHERST is a blockchain- based PKI that implemented rewarding and punishment mechanism using Ethereum ECR-20 token named PKIToken to improve the trustworthiness of information published by the blockchain nodes. In this paper, we implement an Ethereum-based distributed application (dapp) that allowed the community members to act on trusting and untrusting on information provided by any of the members. With the ETHERST framework as the backend, the ETHERSTWEB is equipped with the rewarding and punishment mechanism to keep the community from misusing the trusting and untrusting action to maintain the trustworthiness of information of a member. With the PKIToken amount level implemented in the backend, it provides an index to the trustworthiness of a member in the community. It has the advantages over the existing rating or review systems that are commonly implemented in many traditional web applications.